Validation and Factor Analysis of the Japanese Version of the Highs Scale in Perinatal Women - Yamauchi, Aya; Okada, Takashi; Ando, Masahiko; Morikawa, Mako; Nakamura, Yukako; Kubota, Chika; Ohara, Masako; Murase, Satomi; Goto, Setsuko; Kanai, Atsuko; Ozaki, Norio (Frontiers in Psychiatry, 2018)
Background The Highs scale has been developed to evaluate hypomanic symptoms in the first postpartum week. However, it has not been elucidated whether this scale is also applicable to pregnant women. To address this issue, we confirmed the factor structure, reliability, and validity of the Japanese version of the Highs scale for pregnant and postpartum women. Methods 418 women provided effective responses to both the Highs scale and the Edinburgh Postnatal Depression Scale (EPDS) during early pregnancy (before week 25), late pregnancy (around week 36), at 5 days and at 1 month after delivery. Subjects were randomly divided into two groups, and exploratory and confirmatory factor analyses were performed for each group. Cronbach’s alpha was calculated and the correlation of the Highs scale with EPDS was analyzed. The correlation between the subscales was analyzed at four time points, and the correlation of subscales between the four time points was confirmed. Results This scale was found to have the two-factor structure with elation and agitation subscales. The two subscales had reasonable internal consistency at all time points (Cronbach’s alpha range: Factor 1, 0.696–0.758; Factor 2, 0.553–0.694). The overall scale had reasonable internal consistency at all time points (Cronbach’s alpha range: 0.672–0.738). Based on the correlation analysis of the two subscales and EPDS, discriminative and convergent validity were indicated at all time points, confirming the construct validity of the Highs scale. Subscale scores showed a significant correlation with EPDS at all time points (r = 0.388, 0.384, 0.498, and 0.442, p<0.01). Conclusions The Japanese version of the Highs scale is reliable and valid, and can be applied for evaluating the hypomanic symptoms during pregnancy and postpartum period.